Fuzzified iterative algorithms for performance driven low powerVLSI placement - Sait, Sadiq M. (2001)
In this paper we employ fuzzified simulated evolution and stochastic evolution algorithms for VLSI. standard cell placement targeting low power dissipation and high performance. Due to the imprecise nature of design information at the placement stage, the various objectives and constraints are expressed in fuzzy domain. The search is made to evolve towards a vector of fuzzy goals. The proposed algorithms are compared with genetic algorithm